Respuesta :

Answer:

Step-by-step explanation:

Use the property,

"Measure of an arc is equal to the measure of the central angle subtended by the arc at the center of a circle"

a). m∠JQN = 90°

   Therefore, m(arc JN) = 90°

b). m(arc KL) = m(arc JM) - [m(arc JK) + m(arc LM)]

                     = 180° - (56° + 98°)

                     = 180° - 154°

                     = 26°

c). m(arc NK) = m(arc JN) + m(arc JK)

                     = 90° + 56°

                     = 146°

d). m(arc NML) = m(arc NM) + m(arc ML)

                        = 90° + 98°

                        = 188°

e). m(arc MNL) = m(arc MJ) + m(arc JK) + m(arc KL)

                        = 180° + 56° + 26°

                        = 262°